Carbon nanopowder acts as a Trojan-horse for benzo(α)pyrene in Danio rerio embryos. Issue 3 (16th March 2017) - Binelli, A.; Del Giacco, L.; Santo, N.; Bini, L.; Magni, S.; Parolini, M.; Madaschi, L.; Ghilardi, A.; Maggioni, D.; Ascagni, M.; Armini, A.; Prosperi, L.; et al.
Abstract: Carbon-based nanoparticles (CBNs) are largely distributed worldwide due to fossil fuel combustion and their presence in many consumer products. In addition to their proven toxicological effects in several biological models, attention in recent years has focussed on the role played by CBNs as Trojan-horse carriers for adsorbed environmental pollutants. This role has not been conclusively determined to date because CBNs can decrease the bioavailability of contaminants or represent an additional source of intake. Herein, we evaluated the intake, transport and distribution of one of the carbon-based powders, the so-called carbon nanopowder (CNPW), and benzo(α)pyrene, when administered alone and in co-exposure to Danio rerio embryos. Data obtained by means of advanced microscopic techniques illustrated that the "particle-specific" effect induced a modification in the accumulation of benzo(α)pyrene, which is forced to follow the distribution of the physical pollutant instead of its natural bioaccumulation. The combined results from functional proteomics and gene transcription analysis highlighted the different biochemical pathways involved in the action of the two different contaminants administered alone and when bound together. In particular, we observed a clear change in several proteins involved in the homeostatic response to hypoxia only after exposure to the CNPW or co-exposure to the mixture, whereas exposure to benzo(α)pyrene alone mainly modified structural proteins. The entire dataset suggested a Trojan-horse mechanism involved in the biological impacts on Danio rerio embryos especially due to different bioaccumulation pathways and cellular targets.